Numerical approximation of self-consistent Vlasov models for low-frequency electromagnetic phenomena - Besse, Nicolas; Mauser, Norbert J.; Sonnendrücker, Eric (Zielona Góra: Uniwersytet Zielonogórski)
We present a new numerical method to solve the Vlasov-Darwin and Vlasov-Poisswell systems which are approximations of the Vlasov-Maxwell equation in the asymptotic limit of the infinite speed of light. These systems model low-frequency electromagnetic phenomena in plasmas, and thus "light waves" are somewhat supressed, which in turn allows the numerical discretization to dispense with the Courant-Friedrichs-Lewy condition on the time step.
Keywords: Vlasov-Darwin model; Vlasov-Poisswell model; semi-Lagrangian methods; low-frequency electromagnetic phenomena